Platelet counts and prognosis in heart failure with mildly reduced ejection fraction: results from a large-scaled registry - Dudda, Jonas; Behnes, Michael; Weidner, Kathrin; Lau, Felix; Schmitt, Alexander; Reinhardt, Marielen; Abel, Noah; Bertsch, Thomas; Dürschmied, Daniel; Akın, Ibrahim; Schupp, Tobias (International journal of cardiology, 2026)
Objective - Platelets have been reported to promote heart failure (HF) through prothrombotic and proinflammatory pathways. The present study sought to investigate the prognostic impact of baseline platelet counts in patients hospitalized with heart failure with mildly reduced ejection fraction (HFmrEF). - Background - The association of platelet counts and prognosis in patients with HFmrEF is not well studied. - Methods - Consecutive patients hospitalized with HFmrEF (ie, left ventricular ejection fraction 41-49 % and signs and/or symptoms of HF) were retrospectively included at one institution from 2016 to 2022. Clinical outcome was assessed according to baseline platelet counts comparing patients with 10-450/nL, 100- < 150/nL, 50- < 100/nL, <50/nL and > 450/nL. The primary endpoint was all-cause mortality at 30 months (median follow-up). The key secondary endpoint was HF-related rehospitalization at 30 months. - Results - From a total of 2151 consecutive patients with HFmrEF, the median platelet count was 253/nL (interquartile range (IQR) 196-287/nL). A baseline platelet count <50/nL (HR = 3.487; 95 % CI 2.111-5.760; p = 0.001) and 50- < 100/nL (HR = 1.565; 95 % CI 1.024-2.394; p = 0.036) was associated with increased risk of 30-months all-cause mortality compared to patients with normal platelet counts, which was still demonstrated after multivariable adjustments. In contrast, the presence of higher baseline platelet counts (>450/nL) was not associated with long-term all-cause mortality (HR = 1.140; 95 % CI 0.769-1.690; p = 0.515). Furthermore, no association between platelet count and the risk of HF-related rehospitalization was observed. - Conclusion - In patients hospitalized with HFmrEF, baseline platelet counts of <50/nL and 50- < 100/nL were independently associated with an increased risk of all-cause mortality at 30 months.